The complete chloroplast genome of Pyrus ussuriensis Maxim. (Rosaceae) - Hee-Young Gil; Yongsung Kim; Seon-Hee Kim; Ji-Hyeon Jeon; Youl Kwon; Seung-Chul Kim; Jongsun Park (Mitochondrial DNA. Part B. Resources, 2019)
Pyrus ussuriensis Maxim. is an oriental domesticated pear which have been used as a traditional medicine as well as dominant contributor of many Asian origin pear breeds. Here, we presented complete chloroplast genome of P. ussuriensis which is 160,157 bp long and has four subregions: 88,148 bp of large single-copy (LSC) and 19,227 bp of small singl- copy (SSC) regions are separated by 26,391 bp of inverted repeat (IR) regions including 130 genes (85 protein-coding genes, 8 rRNAs, and 37 tRNAs). The overall GC content of the chloroplast genome is 36.6% and in the LSC, SSC, and IR regions are 34.2%, 30.4%, and 42.7%, respectively. Phylogenetic trees reflect that P. ussuriensis has been utilized as a dominant contributor to many Asian origin pear breeds.